2010
DOI: 10.1016/j.acra.2009.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of a Prototype Dual-Energy Chest Imaging System

Abstract: Purpose: To assess the performance of a Dual-Energy chest radiography system. Methods:A cohort of 129 patients was recruited from population referred for CT guided biopsy of a lung lesion. Digital radiography (DR) and Dual Energy (DE) images were acquired.Receiver operating characteristic (ROC) tests were performed to evaluate performance of DE images compared to DR. Five chest radiologists scored images. Performance was analyzed for all cases pooled and sub groups based on gender, nodule size, density, locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 34 publications
(15 reference statements)
2
18
0
Order By: Relevance
“…This is partly due to the fact that as the lesion size becomes smaller, the advantage of anatomical noise reduction is negated. This is inferred from studies by Kashani et al [9], and Ruhl et al [10], who found no statistically significant difference in detection of pulmonary nodules (based on their size) by addition of DES-DR. Similarly, DT images are affected by the inherent tomographic noise that is related to the limited angle reconstruction involved in this technique.…”
Section: Discussionmentioning
confidence: 74%
“…This is partly due to the fact that as the lesion size becomes smaller, the advantage of anatomical noise reduction is negated. This is inferred from studies by Kashani et al [9], and Ruhl et al [10], who found no statistically significant difference in detection of pulmonary nodules (based on their size) by addition of DES-DR. Similarly, DT images are affected by the inherent tomographic noise that is related to the limited angle reconstruction involved in this technique.…”
Section: Discussionmentioning
confidence: 74%
“…bone or soft tissue) within a 2D radiograph by combining two (or more) images obtained at different x-ray energies [2]. Receiver-operating characteristic studies have shown that dual-energy methods can improve conspicuity of lesions in particular examinations, such as the detection and characterization of small lung lesions, compared to conventional digital radiography for the same patient dose [3].…”
Section: Introductionmentioning
confidence: 99%
“…16,17) The patients with images ranked as definitely present or probably present were classified as ED positive (ED+). A representative picture of ED+ is shown in Figure 2A ( Figure 2B showed its diagnostic angiography) and a case of early defect absent was shown in Figure 2C.…”
Section: Methodsmentioning
confidence: 99%